2020
DOI: 10.1002/jbm4.10344
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Treatments Affect Bone Matrix Maturation in a Rat Model of Induced Cortical Remodeling

Abstract: To test how osteoporosis drugs affect bone matrix maturation during cortical bone remodeling, 72 pregnant rats were switched from a 0.4% to a 0.01% calcium diet at parturition for a 23‐day lactation period. At weaning, eight dams were sacrificed to establish baseline values, while the remaining dams were returned to 0.4% calcium and treated with vehicle (saline), sodium fluoride (NaF), zoledronic acid (ZA), or sclerostin antibody (Scl‐Ab) for either 7 or 28 days (eight animals per group per time point). Femora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, bisphosphonates are known to have positive effects on early implant fixation clinically, 3 as well as osseointegration 42 . Bisphosphonates have also been shown to alter bone matrix composition including crystallinity 6–8 . Based on our results, it is likely that both changes in the bone structure and composition likely contribute to the increased fixation strength reported in preclinical animal models 24 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, bisphosphonates are known to have positive effects on early implant fixation clinically, 3 as well as osseointegration 42 . Bisphosphonates have also been shown to alter bone matrix composition including crystallinity 6–8 . Based on our results, it is likely that both changes in the bone structure and composition likely contribute to the increased fixation strength reported in preclinical animal models 24 .…”
Section: Discussionmentioning
confidence: 58%
“…Bone matrix composition is altered in prevalent diseases relevant to orthopedic surgery such as osteoporosis and type 2 diabetes mellitus (T2DM). While osteoporosis is mainly thought of as a disease of low bone mineral density, both preclinical 5 and clinical observation studies 6–9 have demonstrated that bone matrix composition is also altered by osteoporosis and these alterations contribute to fragility fracture risk 10 . T2DM is another condition known to change bone matrix composition in preclinical 11 and clinical studies, 12,13 which likely contribute to the elevated rates of fragility fracture despite normal bone mineral density 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Additional technical limitations include the lack of tissue age–specific measurements of bone matrix composition and the limited number of individual spectra collected for each animal. Although we have used fluorescent labels in the past to make tissue age–specific measurements on rat tissues, ( 68 ) the Raman instrument we used for this analysis was not equipped with fluorescent imaging. The lack of tissue‐age resolution could increase the intra‐specimen variability in the Raman measurements and prevents us from determining whether the measured matrix changes were due to differences in newly formed bone or changes to existing bone matrix.…”
Section: Discussionmentioning
confidence: 99%